Psychologist. Pedagogue. Person. On the Anniversary of Tatiana Germanovna Goryacheva - E.O. Sedova (Клиническая и специальная психология)
Remarkable Russian neuropsychologist, the author of the sensory-motor correction method Tatiana Germanovna Goryacheva celebrates her anniversary in December of 2024. The article describes the milestones of her biography and marks out the main scientific interests, among them: psychology of abnormal development, neuropsychological correction, child psychosomatics. Many years of practical activity in the sphere of child neuropsychology have been mentioned and pedagogical talent of Tatiana Goryacheva has been emphasized. The staff of the Institute of Clinical Psychology and Social Work of the Pirogov RNRMU as well as the Department of Neuro- and Patho-psychology of Development at MSUPE cordially congratulates Tatiana Germanovna on her anniversary wishing her a good health and success in scientific and practical activity.